Effects of left atrium on intraventricular flow in numerical simulations. (March 2019) - Su, Boyang; Wang, Xikun; Kabinejadian, Foad; Chin, Calvin; Le, Thu Thao; Zhang, Jun-Mei
Abstract: With the aid of cardiac imaging techniques, recent numerical simulations of left ventricular flow can be patient-specific to better mimic physiological conditions. However, studies with a dynamic mitral valve (MV) remain extremely limited. Even so, the left atrium (LA) is usually simplified to be tubular regardless of its complex structure. Studies on the effect of this simplification are limited and observations are controversial. In this study, both tubular and generic atriums were incorporated in patient-specific simulations with and without the MV to qualitatively and quantitatively estimate the effects of the atrial model on downstream ventricular flow. The patient-specific model was generated based on cardiac magnetic resonance (CMR) images of a healthy volunteer, and the dynamic motion of the MV was defined by the contours acquired along long-axis images. Based on the simulations, the influence of the atrial vortices on ventricular flow was significant in the valveless models in terms of flow structure, kinetic energy (KE) and circulation. Although these effects were suppressed in the presence of the MV, the atrial vortices that survived the passage were not trivial, which was evidenced by reduced strength of circulation and undesired flow pattern in the apical region. The flow structure in the generic atrium also dominated the development of ventricular flow in the valveless model. After the MV was incorporated, its effects on the downstream ventricular flow were considerably reduced but not eliminated. Therefore, a proper modelling of atrial flow is necessary, especially for subjects with high ejection fraction (EF). Highlights: The effect of atrial flow on a patient-specific left ventricular flow has been investigated. The atrial vorticies dominated the ventricular flow when the mitral valve was absent in the numerical model. The impacts of atrial vortices were significantly suppressed by the mitral valve but not completely eliminated. The survived atrial vorticies through mitral valve were capable of altering the apical flow and circulation. It is reasonable to properly model atrial flow, especially for subjects with high ejection fraction.